THE RESTORATIVE COSMETIC CONSTITUENTS OF Fragraea fragrans FRUITS - Dasril Basir; Julinar Julinar (Indonesian Journal of Chemistry, 2012)
This paper describes 3-hydroxyurs-12-en-28-oic acid and its structural isomer 3-hydroxyolean-12-en-28-oic acid isolated from Fragraea fragrans fruits and their biological activities; anti-tumor, anti-inflammation, anti-microbial, and anti-fungal included their ultra violet photo-protective effect after exposed under sunlight radiation. They are useful for cosmetic ingredient. The above triterpenes are very promoting compounds for leukemia L1210 anti-tumor due to limited reports dealing with this type triterpenoid anti-tumor test. They significantly gave IC50 value of 5.78 µg/mL against leukemia L1210 cells, relatively closed to IC50 value of drugs, 4.0 µg/mL [12-13,17].